Peel and peel again. Issue 3 (30th November 2007) - Gibran, S K; Flemming, B; Stappler, T; Pearce, I; Groenewald, C; Heimann, H; Hiscott, P; Wong, D
Abstract : Aim: To determine if the internal limiting membrane (ILM) was present in the epiretinal membrane (ERM) when we deliberately tried to perform a "double peel" for macular pucker. Methods: Pars-plana vitrectomy and a "double peel" were carried out. The ERM and ILM were stained with Trypan Blue and peeled separately over the same area. The amount of ERM present in ILM specimens and the amount of ILM present in ERM specimens were evaluated by histological examination. Results: Seventeen eyes in 17 patients were included. It was possible to double peel in all cases. Five of 17 ERM specimens (29%) contained ILM fragments. When ILM was present on the ERM, it represented less than 50% of the sample. One ILM specimen was lost as result of an administrative error; of the remaining 16 specimens, residual ERM was found in six, and cellular remnants were observed on the vitreous surface in a further six of the ILMs. Clinically, no recurrence of ERM was found. Conclusion: ILM was present in some ERM specimens seemingly over the same area that an intact ILM was subsequently peel. We speculate that the ILM in the ERM represent a secondary basement membrane and that the surgical plane of dissection for most ERM peel is between the ERM and the native ILM, making it feasible to double peel routinely.